Radiologic features and treatment outcomes of pulmonary metastasis in gestational trophoblastic neoplasia - Suprasert P. (2014)
Objective: To evaluate the radiologic patterns and treatment outcome of pulmonary metastasis in patients with gestational trophoblastic tumor (GTT). Material and Method: The medical records and chest films of GTT patients treated at Chiang Mai University Hospital between January 1998 and June 2003 were reviewed. Results: There were 85 GTT-patients in the study period. 32 cases (37.6%) had pulmonary metastasis diagnosed with chest X-rays. The most common radiologic pattern was well defined nodule. The radiologic features of patients who had lung metastases alone were not significantly different from those who had associated metastases in other organs. 27 patients (84.3%) received multiple chemotherapy and 6 required more than one regimen. The mean number of chemotherapy was 7 cycles (range 3-23). Adjuvant surgery consisted of hysterectomy (11), salpingo-oophorectomy (1), thoracotomy (2), and craniotomy (1). Four patients received whole brain irradiation for brain metastases. Among 10 patients with lung metastasis alone, 8 (80%) attained complete remission, the remaining 2 patients were lost to follow-up. Among 22 patients with associated multiple organ metastases, 16 (72.7%) had complete remission, 2 died from diseases, 4 were lost to follow-up. Conclusion: The most common radiologic pattern of pulmonary metastasis in GTT patients was well-defined multiple lung nodules. The radiologic features of patients who had lung metastases alone were not significantly different from those who developed metastases in other organs.